2017
DOI: 10.1136/archdischild-2016-312286
|View full text |Cite
|
Sign up to set email alerts
|

Using exhaled CO2to guide initial respiratory support at birth: a randomised controlled trial

Abstract: NCT01739114; Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…However, a recent randomised trial comparing SI with positive pressure ventilation alone by our group did not find any difference in either pneumothoraxes and intraventricular haemorrhages 26. Similar, in the current trial we observed similar rates of pneumothoraxes and intraventricular haemorrhages between groups (table 2).…”
Section: Discussionsupporting
confidence: 89%
“…However, a recent randomised trial comparing SI with positive pressure ventilation alone by our group did not find any difference in either pneumothoraxes and intraventricular haemorrhages 26. Similar, in the current trial we observed similar rates of pneumothoraxes and intraventricular haemorrhages between groups (table 2).…”
Section: Discussionsupporting
confidence: 89%
“…A second limitation was the smaller sample size which affected the statistical analysis of smaller populations and groups, most notably SGA infants. While two separate RCTs were combined for this study, they both occurred within an overlapping 16-month time period within the same hospital and with identical treatment protocols aside from the respiratory treatment intervention; therefore, no significant difference in treatment is likely to have affected hypoglycemia (10,11). In addition, this study examined the transition phase immediately after birth.…”
Section: Discussionmentioning
confidence: 99%
“…This was a secondary analysis from infants enrolled in previously published randomized controlled trials in premature infants (10,11). The studies were carried out at The Royal Alexandra Hospital in Edmonton, Alberta, Canada, a tertiary perinatal center admitting more than 350 infants with a birth weight of <1,500 g annually.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, concerns regarding the safety of this technique still need to be clarified. A potential method could be end-tidal CO 2 (ETCO 2 ) monitoring, which have shown to be feasible to guide length of SI during resuscitation [38]. Also, the effectiveness of SI maneuver can be largely influenced by several factors, such as the different skill of the clinical team, interface through which a SI is delivered [39], the infant's respiratory effort [35] and mask leak [32].…”
Section: Sustained Inflationmentioning
confidence: 99%